Childlessness no brasil: a contribuição das mudanças sociodemográficas para a tendência de zero filho - Victor Antunes Leocádio (2018)
In Brazil, between the birth cohorts from 1942-1946 to 1966-1970, there was an increase of almost 50% in the proportion of women who completed the reproductive period without a child – what was 9.03% in the oldest cohort, became 13.53% in the most recent. This rising trend was accompanied by changes in the composition and association of variables such as education and union status. Considering this context, this work aims to analyze the contribution of changes in composition and rate components in the explanation of the rising trend of permanent childlessness in Brazil, that is, investigate the contribution of sociodemographic changes in this proportional increase of women without children. The analysis takes place through 6 birth cohorts, ranging from 1942 to 1970, obtained from data of women aged 40 to 49 years in the 1991, 2000 and 2010 censuses. The methods used are binary logistic regression and decomposition based on regression. The results show that, in aggregate, both components contribute to the proportional increase of childlessness, with a slight advantage for the changes in the reproductive behavior. Analyzing the contribution of each of the variables, changes in education had a greater impact than changes in the union status. More specifically, the contributions of each of the variables categories show that the increase in childlessness is attributable mainly to two changes: composition of women with elementary incomplete and reproductive behavior of women who have already lived with their partners. The results of this work suggest and discuss a possible loosening/untying of the relationship between union and reproduction, as well as an increase in permanent voluntary childlessness.